The Role of Ikhlas in The Bdi Model: Enhancing Green Agriculture Practices Among Rural Communities - Riska, Riska; Razak, Syaparuddin; Keri, Ismail (JURNAL EKONOMI SYARIAH, 2025)
Introduction to The Problem: This study explores the role of sincerity in the BDI (Belief, Desire, Intention) model to promote green agriculture among rural communities in Kecamatan Palakka. The study addresses the need to understand how belief, desire, ikhlas (sincerity), and intention influence decisions to adopt green agricultural practices.Purpose/Objective Study: The main objectives are to identify the effects of belief, desire, ikhlas, and intention on adopting green agriculture and to examine the mediating role of intention in this relationship.Design/Methodology/Approach: An integrative approach combining quantitative methods and Islamic economics was employed. Data were collected via a questionnaire survey of 152 respondents with experience or potential in green agriculture and analyzed using Structural Equation Modeling (SEM).Findings: The results indicate that belief, desire, and ikhlas significantly influence intention and the decision to adopt green agriculture. Intention serves as a strong mediator, with sincerity, belief, and desire enhancing the willingness and commitment to green farming practices.